RETRACTED ARTICLE: NR3C2 affects the proliferation and invasiveness of colon cancer cells through the Wnt/β-Catenin signaling pathway - Ke Nie; Zhong-Jiang He; Ling-Jun Kong (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose The aim of this study was to explore the potential correlation between the nuclear receptor subfamily 3 group C member 2 (NR3C2) and outcomes of colon cancer, along with the mechanisms underlying this association. Method mRNA (messenger RNA) data and clinical records pertaining to colon cancer were retrieved from The Cancer Genome Atlas (TCGA) database. The analysis of NR3C2 expression discrepancies between normal colon and tumor tissues was conducted using R software. In addition, we also studied the relationship between NR3C2 expression and prognosis, pathological parameters. The relative role of NR3C2 were further predicted through bioinformatics methods and receiver operating characteristic (ROC) curve was used to evaluate the diagnostic value of NR3C2 in colon cancer. Single-cell data from colon cancer samples in the GEO (Gene Expression Omnibus) database further investigated the mechanism of the lower survival associated with NR3C2 dysregulation. NR3C2 expression in three fresh colon cancer samples and their respective paracancer samples was determined. Furthermore, colon cancer cell models overexpressing NR3C2 and with knockdown NR3C2 were constructed by lentiviral vector transfection. Cell Counting Kit-8 assay, transplantation of tumors in nude mice and transwell assays were used to examine the proliferation, migration and invasion of colon cancer cells. The effect on the Wnt/β-catenin pathway, activities of cellular autophagy and cell apoptosis were examined by assessing the expression levels of several key proteins, including Bcl-2, Bax, and LC3. Results We found that NR3C2 was found a significantly lower level in colon cancer tissues than in adjacent tissues, which was associated with distant and lymphatic metastases, clinical stage, and poor clinical outcome, and it was an independent prognostic factor and potential marker of colon cancer. Single-cell transcriptome data identified the subset of circulating T and B cells with high expression of NR3C2, which is involved in TNF signaling pathway. Functional experiments show that downregulation of NR3C2 resultsed in the activation of the Wnt/β-catenin signaling pathway, and promotesd the proliferation and invasion of colon cancer cells while suppressing cell autophagy and apoptosis. Conclusion NR3C2 may regulate Wnt/β-catenin to affect the proliferation, invasion apoptosis and autophagy of colon cancer, and this axis is a potential target for the treatment of colon cancer.